Explorando el suelo con un enfoque didáctico a través de un prototipo antiadherente biomimético - Sainz, Daiana Soledad; La Fuente, Lorena Beatriz; Espinosa, Juan Alberto; Favret, Eduardo Alfredo; Contardo, Lucía; Otero Estrada, Edit; Rodriguez, Analia; Gonzalez, Mauro Andres; Flamenco, Natali; Pattini, Miriam Graciela; Setten, Lorena (Asociación Argentina Ciencia del Suelo, 2024)
Poster